The Cardiovascular Health in Ambulatory Care Research Team (CANHEART): Using Big Data to Measure and Improve Cardiovascular Health and Healthcare Services. (March 2015) - Tu, Jack V.; Chu, Anna; Donovan, Linda R.; Ko, Dennis T.; Booth, Gillian L.; Tu, Karen; Maclagan, Laura C.; Guo, Helen; Austin, Peter C.; Hogg, William; Kapral, Moira K.; Wijeysundera, Harindra C.; et al.
Abstract : Background—: The CArdiovascular HEalth in Ambulatory care Research Team (CANHEART) is conducting a unique, population-based observational research initiative aimed at measuring and improving cardiovascular health and the quality of ambulatory cardiovascular care provided in Ontario, Canada. A particular focus will be on identifying opportunities to improve the primary and secondary prevention of cardiovascular events in Ontario's diverse multiethnic population. Methods and Results—: A population-based cohort comprising 9.8 million Ontario adults ≥20 years in 2008 was assembled by linking multiple electronic survey, health administrative, clinical, laboratory, drug, and electronic medical record databases using encoded personal identifiers. The cohort includes ≈9.4 million primary prevention patients and ≈400 000 secondary prevention patients. Follow-up on clinical events is achieved through record linkage to comprehensive hospitalization, emergency department, and vital statistics administrative databases. Profiles of cardiovascular health and preventive care will be developed at the health region level, and the cohort will be used to study the causes of regional variation in the incidence of major cardiovascular events and other important research questions. Conclusions—: Linkage of multiple databases will enable the CANHEART study cohort to serve as a powerful big data resource for scientific research aimed at improving cardiovascular health and health services delivery. Study findings will be shared with clinicians, policy makers, and the public to facilitate population health interventions and quality improvement initiatives. Abstract : Supplemental Digital Content is available in the text.